2014
DOI: 10.2527/jas.2014-7713
|View full text |Cite
|
Sign up to set email alerts
|

Use of a stair-step compensatory gain nutritional regimen to program the onset of puberty in beef heifers1

Abstract: It was hypothesized that metabolic programming of processes underlying puberty can be shifted temporally through the use of a stair-step compensatory growth model such that puberty is optimally timed to occur at 11 to 12 mo of age. Forty crossbred beef heifers were weaned at approximately 3.5 mo of age and, after a 2-wk acclimation period, were assigned randomly to 1 of 4 nutritional groups: 1) low control (LC), restricted feed intake of a forage-based diet to promote BW gain of 0.5 kg/d until 14 mo of age, 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 33 publications
2
41
2
4
Order By: Relevance
“…Nelore crossbred heifers had a higher heterozygosity, possibly due to a better adaptation to reach earlier puberty as described by Monteiro et al (2013). Interestingly, it was also observed that heifers fed a high concentrate diet showed a continuously high rate of body weight gain after weaning (Cardoso et al, 2014). Thus, the evaluation of different crossbred phenotypic trends for body growth on a well-controlled nutritional regimen is important to achieve a significant improvement in growth efficiency of heifers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nelore crossbred heifers had a higher heterozygosity, possibly due to a better adaptation to reach earlier puberty as described by Monteiro et al (2013). Interestingly, it was also observed that heifers fed a high concentrate diet showed a continuously high rate of body weight gain after weaning (Cardoso et al, 2014). Thus, the evaluation of different crossbred phenotypic trends for body growth on a well-controlled nutritional regimen is important to achieve a significant improvement in growth efficiency of heifers.…”
Section: Discussionmentioning
confidence: 96%
“…The reproductive neuroendocrine postnatal system accelerates puberty during earlier calfhood, from 3 to 4.5 months of age, which might be facilitated by early programming of leptin secretion in adipose tissue during juvenile development using a stair-step nutritional regimen (Cardoso et al, 2014). Recently, Alves et al (2015) described that the reduction in neuropeptide-Y innervation of gonadotropin-releasing hormone neurons occurs in response to elevated body weight gain during the juvenile period.…”
Section: Discussionmentioning
confidence: 99%
“…The TF PPARG was previously identified as a key regulator of cattle puberty, in a network prediction from genomewide association data (Fortes et al, 2010). It is feasible to speculate that PPAR signaling is important for puberty, because of its relevance to fat metabolism and the well-known interplay between nutrition, metabolism, and puberty in cattle (Cardoso et al, 2014(Cardoso et al, , 2015.…”
Section: Pituitary Gland Genes: Differentially Expressed and Interactingmentioning
confidence: 99%
“…Entretanto, há uma desvantagem relacionada ao plano nutricional deficiente ou excessivo imposto às vacas, o que pode refletir em falhas no ciclo estral, ausência de prenhez e crias com desempenho atrasado (LANNA et al, 2011 Até agora, trabalhos demonstraram o impacto na idade da puberdade com suplementação no último trimestre de gestação (Funston et al, 2010) e antes do desmame (Gasser et al, 2006a;Cardoso et al, 2014). O último trimestre de gestação é um período que os bezerros podem passar por desnutrição em sistemas de pastagem, e antes do desmame (creep-feeding) é um período em que o ganho de peso dos bezerros pode ser melhorado.…”
Section: Suplementação Proteica De Vacas De Corteunclassified